Effectiveness of brief cognitive behavioural therapy for non-underweight eating disorders in Iceland - Jakob Fannar Stefánsson 1995- (2022)
Objective: Long waitlists and scarce resources for psychological treatment in the Icelandic healthcare system call for improvements. As cognitive behaviour therapy for eating disorders (CBT-ED) is effective and the predominant treatment for non-underweight patients, justification for the use of the brief ten-session form of CBT-ED, CBT-T is in place. CBT-T has shown comparable results to CBT-ED in other countries. Outcomes of CBT-T for non-underweight eating disorders in Iceland are unknown and worthwhile to explore. Method: For 14 months 33 patients were allocated to CBT-T and their outcomes were used in this study. The manualized ten-session form, CBT-T, with two follow-up sessions was provided by psychologists and clinicians at the eating disorder clinic of the National University Hospital of Iceland. Measures assessed the patient’s eating disorder pathology, symptoms of depression, anxiety, and stress as well as their quality of life. A mixed-model repeated-measures analysis was used to assess outcomes. Results: CBT-T is an effective treatment for non-underweight eating disorders with a typical drop-out rate. Remission for patients that completed the treatment seems to be stable over a 3-month follow-up. Most patients that completed the treatment went from being over the cut-off point on EDE-Q at the start of treatment to under cut-off at end of treatment, as well as having a significant remission in disordered eating behaviours. Discussion: The ten-session CBT-T is a valuable treatment option for non-underweight patients at the Eating Disorder Clinic in Iceland. The treatment effectiveness is comparable to earlier studies of CBT-T. The cost-benefit of a shorter but effective treatment for eating disorders is evident.